2014
DOI: 10.1148/rg.347140025
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Barriers to Timely MR Imaging Scheduling

Abstract: Scheduling a magnetic resonance (MR) imaging study at the authors' large health system in 2011 required considerable preparation before an appointment time was given to a patient. Difficulties in promptly scheduling appointments resulted from the varying time required for examinations, depending on the requested protocol, availability of appropriate MR imaging equipment, examination timing, prior insurance authorization verification, and proper patient screening. These factors contributed to a backlog of patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 15 publications
0
6
0
2
Order By: Relevance
“…These include the frequent lack of availability in the emergency department or at urgent care centers, the need for prior insurance authorization, and proper patient screening. 34 Although our study found that obtaining an MRI was a risk factor for a delay in surgery, this does not imply that it should not be part of the pretreatment evaluation for TSFs. Rather, to limit surgical delays, MRI should be ordered judiciously and obtained promptly after initial evaluation.…”
Section: Discussionmentioning
confidence: 58%
“…These include the frequent lack of availability in the emergency department or at urgent care centers, the need for prior insurance authorization, and proper patient screening. 34 Although our study found that obtaining an MRI was a risk factor for a delay in surgery, this does not imply that it should not be part of the pretreatment evaluation for TSFs. Rather, to limit surgical delays, MRI should be ordered judiciously and obtained promptly after initial evaluation.…”
Section: Discussionmentioning
confidence: 58%
“…After targeting any article that combined the terms ''patient flow'' with ''diagnostic imaging'', 14 useful articles were retrieved. 1,2,[4][5][6][7][8][9][10][11][12][13][14][15] Reviewing the literature provided a wealth of knowledge and a multitude of frameworks for analysing and improving patient flow. Additionally, several gaps in the literature were identified, including the possible benefit(s) of utilizing personnel such as Technologist Assistants (TA) or DIdedicated porters.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Используя принципы бережливого производства (lean manufacturing) применительно к лучевой диагностике [2][3][4][5][6][7] и оригинальную методологию компании Philips, мы выполнили комплексную оценку работы отделения компьютерной и магнитно-резонансной томографии Центра лучевой диагностики Лечебно-реабилитационного центра (ЦЛД ЛРЦ) в период с декабря 2016 г. по февраль 2017 г.…”
Section: материал и методыunclassified